Analysis and Design of Elementary MOS Amplifier Stages - Murmann, Boris (Open textbook library., 2013)
Analyzes core linear analog circuit designs: common-source, common-gate, and common-drain stages Design-oriented approach; analyzes various circuits through examples and exercises Part of the Modular Series of Microelectronic Device and Circuit Design Each module in the series provides a brief fundamental look at a specific topic "As of November 1, 2022, National Technology and Science Press ("NTS") has discontinued publication of 'Analysis and Design of Elementary MOS Amplifier Stages.' Accordingly, NTS has returned all copyrights and attendant rights with respect to the work to Boris Murmann."